Cover Picture: Fast Prediction of Adsorption Properties for Platinum Nanocatalysts with Generalized Coordination Numbers (Angew. Chem. Int. Ed. 32/2014). Issue 32 (24th June 2014) - Calle‐Vallejo, Federico; Martínez, José I.; García‐Lastra, Juan M.; Sautet, Philippe; Loffreda, David
<x xml:space="preserve">Abstract</x> In heterogeneous catalysis and fuel‐cell design, the fast and accurate prediction of chemical reactivity is paramount. Current theoretical models use electronic‐structure‐based descriptors with known limitations. D. Loffreda et al. demonstrate in their Communication on page 8316 ff. that the adsorption energetics of oxygenated species on various platinum nanoparticles and surfaces are linearly captured by a non‐electronic, exact, and powerful descriptor: the generalized coordination number.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>